2015
DOI: 10.3390/ma8074544
|View full text |Cite
|
Sign up to set email alerts
|

Towards InAs/InGaAs/GaAs Quantum Dot Solar Cells Directly Grown on Si Substrate

Abstract: This paper reports on an initial assessment of the direct growth of In(Ga)As/GaAs quantum dots (QDs) solar cells on nanostructured surface Si substrate by molecular beam epitaxy (MBE). The effect of inserting 40 InAs/InGaAs/GaAs QDs layers in the intrinsic region of the heterojunction pin-GaAs/n+-Si was evaluated using photocurrent spectroscopy in comparison with pin-GaAs/n+-Si and pin-GaAs/GaAs without QDs. The results reveal the clear contribution of the QDs layers to the improvement of the spectral response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…However, it is noteworthy that an increase in photon energy above ε g leads to a slight decrease of the photoresponse. Naturally, this confirms that metamorphic QDs, despite being effective recombination centers [ 1 , 2 , 12 , 22 ], are more efficient contributors to photocurrent than MB [ 5 , 6 , 23 ].…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…However, it is noteworthy that an increase in photon energy above ε g leads to a slight decrease of the photoresponse. Naturally, this confirms that metamorphic QDs, despite being effective recombination centers [ 1 , 2 , 12 , 22 ], are more efficient contributors to photocurrent than MB [ 5 , 6 , 23 ].…”
Section: Resultsmentioning
confidence: 56%
“…Metamorphic InAs QD structures have found successful applications in the design and fabrication of IR photonic and light-sensitive devices, such as lasers [ 19 , 20 ], single-photon sources [ 3 , 7 , 21 , 22 ], and solar cells [ 23 25 ]. In(Ga)As QD photodetectors based on interband and intersubband transitions are currently actively investigated for enhanced detection from near-IR to longwave-IR ranges due to their response to the irradiation at normal incidence [ 26 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to these peculiar properties, such nanostructures have found successful applications in the design and fabrication of infrared (IR) photonic and light-sensitive devices, such as QD lasers [28,29], single-photon emitters [30][31][32], and solar cells [33][34][35]. Very recently, we have shown that normal incident light at 1.3-1.55 μm is absorbed by metamorphic QD structures, based on photocurrent (PC) measurements [36].…”
Section: Introductionmentioning
confidence: 99%
“…As well, there have been hopeful attempts to apply the photoelectric properties of the metamorphic InAs QD structures on the design of such light-sensitive devices as metamorphic infrared photodetectors [ 11 13 ] and solar cells [ 37 39 ]. Some studies were carried out to develop structure design [ 25 , 31 – 33 ] and other ones to improve photoelectric properties [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Photovoltage (PV) or photoconductivity (PC) studies is an ideal tool for the determination of the photoresponse as function of light energy, transitions between levels, carrier transport, and operating range of the device [ 10 , 43 , 44 ]. However, despite that some studies of the photoelectric properties of structures with metamorphic InAs QDs have been performed in last years [ 37 39 , 43 ], full aspects of the photoresponse mechanism still remain unclear, as along with the influence of the MB on the properties of the nanostructures. In particular, effects of the GaAs substrate and related interfaces on the photoelectric spectra of InAs/InGaAs/GaAs QD structures have not been explored in details.…”
Section: Introductionmentioning
confidence: 99%